Community Hospital Satisfaction Analysis Based on Structural Equation Model: A Primary Medical Service Survey in China - Jian Huang (Forest Chemicals Review)
The rural population accounts for 80 percent in China. The government should attach great importance to people’s demand for medical care and ensure that the medical achievements of socialist construction benefit the common people and fulfil the grand goal of building a healthy China. Based on customer behavior theory, this study investigates community hospitals, and analyzes the influence of community patient satisfaction, aiming to explore ways to improve patient satisfaction. This research adopts the method of questionnaire survey. Totally 1000 community hospital patients participated in this survey on the attitude of patient toward community hospitals, and 826 valid questionnaires were collected. Structural equation model is adopted to explore 8 latent variables including medical environment, supplementary services, medical configuration, service quality, health care costs, perceived value, patient complaints, patient recognition that affect patient satisfaction mechanism, and the direct effect and indirect effect are analyzed. Finding that among the 8 latent variables, patient complaints and perceived value have the greatest impact on the patient’s satisfaction. In addition, solving patient complaints also significantly influence patients’ recognition of hospitals. This paper discusses the results of the research, and proposes methods and measures to improve patient satisfaction in community hospitals. The data of this research were directly collected from patients in community hospitals, which is of great practical significance in improving the medical service of community hospitals in China, and provides important solutions to the problem of improving the competitiveness of community hospitals compared with large hospitals.